The use of film tourism as a marketing strategy for post-pandemic tourism in The UK - Putri, Rhizna Aulia; Rasyidah, Resa (International Journal of Applied Sciences in Tourism and Events, 2025)
Tourism is an important sector that contributes to the country's annual income. However, the COVID-19 pandemic, which has restricted tourist mobility, has decreased the number of visits to tourist destinations in various countries. Literature on the role of film and its involvement in post-pandemic tourism recovery strategies as a destination marketing tool is still limited. This study aims to analyze the strategy implemented by the United Kingdom in promoting tourist destinations by utilizing the potential of film tourism. This research was conducted using qualitative research methods with thematic analysis of secondary data in the form of policy documents, promotional activities, and case studies in the United Kingdom. The film tourism theory was used as a theoretical framework to understand the role of films in shaping destination branding and influencing visitation motivation. The results of this study indicate that the UK's efforts to promote film tourism destinations are driven by government policies that support film production processes, the availability of websites related to film tourism, and collaboration with various stakeholders from diverse backgrounds. However, film tourism destinations in the UK receive insufficient promotion from film studios and actors, making further collaboration in destination marketing crucial.